On the R&D giants' shoulders: Do FDI help to stand on them? - Sandro Montresor; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2014)
The paper investigates the extent to which outward FDI affect the MNC's capacity of entering (and remaining in) the club of top R&D world investors, benefiting from performance gains in both financial and economic markets. By merging the European Industrial Research and Innovation Scoreboard with the fDi Markets dataset, we find supporting evidence. Increasing the number of FDI projects helps firms overcome the discontinuities that, in the distribution of R&D expenditures, separate the group of the largest world R&D investors from the top of them. The same is true for the number of FDI projects in R&D, which are also more important than greater FDI portfolios in becoming a top R&D spender. Furthermore, unlike FDI in general, more FDI in R&D guarantee firms to remain in this top club of firms as it increases their capacity of resisting competition for a place among the top R&D spenders. Results at the extensive margin (i.e. the number of FDI projects) are confirmed with respect to the scale of FDI projects (i.e. at the intensive margin). However, increasing their size is not enough to become one of the highest ranking R&D firms. Policy implications about the support to R&D internationalisation are drawn accordingly.
Keywords: O32; F23; O33; 330; Foreign Direct Investments (FDI); Multinational Corporations (MNC); Research & Development (R&D).